2020
DOI: 10.1515/iss-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in glioma’s microenvironment

Abstract: ObjectivesGlioma is the most common tumor of the central nervous system. In this review, we outline the immunobiological factors that interact with glioma cells and tumor microenvironment (TME), providing more potential targets for clinical inhibition of glioma development and more directions for glioma treatment.ContentRecent studies have shown that glioma cells secrete a variety of immune regulatory factors and interact with immune cells such as microglial cells, peripheral macrophages, myeloid-derived suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 124 publications
(87 reference statements)
0
20
0
Order By: Relevance
“…This might contribute to the higher ability of these cells to invade the brain parenchyma persistently. Additionally, it has been shown that immune cells, including macrophages and microglia, also promote glioma invasion [48][49][50] . Considering that our experiments were performed in immunodeficient NOD-SCID mice, it remains to be elucidated whether interactions with immune cells potentially affect the invasive behaviour of glioma cells with different GFAPδ/α ratios.…”
Section: Discussionmentioning
confidence: 99%
“…This might contribute to the higher ability of these cells to invade the brain parenchyma persistently. Additionally, it has been shown that immune cells, including macrophages and microglia, also promote glioma invasion [48][49][50] . Considering that our experiments were performed in immunodeficient NOD-SCID mice, it remains to be elucidated whether interactions with immune cells potentially affect the invasive behaviour of glioma cells with different GFAPδ/α ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The tumour microenvironment is considered to play a key role in tumour cell invasion. Mounting evidence indicates that inflammatory factors are found in the tumour microenvironment of many cancers 4 . Pro‐inflammatory factors have been described in glioma, and it is generally considered that IL‐6, IL‐8, CXCL1, CXCL10 and TGFβ2 are pro‐tumour cytokines closely related to glioma progression 5‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…factors are found in the tumour microenvironment of many cancers. 4 Pro-inflammatory factors have been described in glioma, and it is generally considered that IL-6, IL-8, CXCL1, CXCL10 and TGFβ2 are protumour cytokines closely related to glioma progression. [5][6][7][8][9] Interleukin-6 (IL-6) is a cytokine that regulates immune and inflammatory reactions.…”
mentioning
confidence: 99%
“…The profile of residual and non-residual cells in glioma seems to be associated with distinct molecular properties. For glioma, it is reported that M2 (anti-inflammatory macrophage phenotype) is activated via pro-cancerogenic IL-10 and TGF-beta (transforming growth factor) [ 111 ]. Exosomes from glioma cells of the hypoxic niche glioma foster M2 polarization [ 112 ].…”
Section: The Tme Immune-state Is Receptive To the Molecular Heterogen...mentioning
confidence: 99%